Raja Ali Haji dan Pemikiran Kebahasaannya: Studi Terhadap Kitāb Bustan Al-khatibin li As-subyān al-Muta’allimin. - M Mustari (Al-Jami'ah Research Centre, 1998)
At the time when the political, military and economic power of the Riau Empire went down as a consequence of the colonialization and division of Melayu into two poles, Singapore and Semenanjung Tanah Melayu (the North Melayu was under the colonialization of the British) and the islands of Riau (the South Melayu was under the colonialization of the Dutch), people were eager to preserve the Melayu and Islamic traditional values which were inherited from their ancestors. This event, in turn, raised some defensive fights by means of the Islamic culture and languages. Kitab Bustan al-Katibin of Raja Ali Hajjis one of the scholarly answers to the need of the Melayu grammar, which, at the sometime, helps to set the character of Riau as a center for culture and language training in the 19” century. As the first book of Melayu grammar, this book, on the one hand, could fill the lacunae of resources on the subject. But on the other hand, the kitab was not successful enough to satisfy the need for a good grammar book which represents the character of the Melayu language, it only absorbed the Arabic grammar. Thus, the significance of the book lies on Raja Ali Haji's thought of Islam, language, and Melayu, and not on the aspect of the grammar. In short, the